Abstracts of Symposium II: Acute Coronary Syndrome: The Obstructive Plug - Symposium II: Acute Coronary Syndrome: The Obstructive Plug (ACI (Acta Cardiologia Indonesiana), 2018)
Abstracts of Symposium II: Acute Coronary Syndrome: The Obstructive Plug